Liquid Chromatography-Mass Spectrometry (LC-MS) Applications in Food Safety–Review - Sarkate, Pradeep (Journal of Food Science and Hygiene, 2024)
One of the primary goals and aims of studying chemistry in society is the promotion of the well-being of humanity and the sustainable utilization of the available resources. Chemistry has played a significant role in water treatment, food production, energy production, and medicine, among other critical areas of society. This study explored the utilization of liquid chromatography-mass spectrometry in the aspect of promoting food safety for human consumption. Various factors might affect the composition and storage of the food items in the society. Through the utilization of chemistry techniques such as (LC-MS), there can be Identification of the various aspects that require consideration in the Improvement of the different health and nutritional requirements that the food items are expected to have in society. As illustrated in this study, the analytical and technical aspects are highly influential in the determination of the proper measures for each component and the illustration of the various toxins that are likely to affect the overall food safety of the members of society in general.
Keywords: Liquid chromatography; Food Safety; Chemistry; Mass spectrometry